APPLICATION VOLUMES AND SIZES OF DROPLETS FOR THE APPLICATION OF DIQUAT HERBICIDE IN THE CONTROL OF Eichhornia crassipes - Almeida, D. P. [UNESP]; Agostini, A. R. [UNESP]; Yamauchi, A. K. [UNESP]; Decaro, Jr. S. T. [UNESP]; Ferreira, M. C. [UNESP] (Univ Federal Vicosa, 2016)
The objective of this study was to evaluate the efficiency of application and the efficacy of control of water hyacinth (Eichhornia crassipes) with the use of the diquat herbicide done with two application volumes associated to three droplets classes. Three experiments were conducted; in the first, the application efficiency was evaluated; in the second, the control efficiency and; in the third, the droplet spectrum. They were conducted in a completely randomized design with five, four and six replicates, respectively. The treatments were arranged in a 2 x 3 factorial design, with two application volumes (100 and 200 L ha(-1)) and three droplets classes (fine, extremely coarse and ultra-coarse) to the first and second experiment and the third comprised two diquat concentrations in spray solution (2 and 4 g i.a. L-1) and three droplets classes (fine, extremely coarse and ultra-coarse). The application efficiency was determined by the coverage by droplets, spray deposition and active ingredient of the herbicide (diquat). The efficacy was measured by the control and the percentage of plants with regrowth at 50 days after application. The spectrum of droplets produced per each nozzle model used to obtain the droplets classes were analyzed. According to the parameters analyzed, using the droplets classes extremely thick and ultra thick can provide greater certainty in the application of diquat in the aquatic environment associated with the deposition of the active and sufficient coverage to control Eichhornia crassipes with both application volumes
Keywords: spray volume; volume median diameter; chemical control of aquatic plants